Thymoma and Synchronous Primary Mediastinal Seminomas with Florid Follicular Lymphoid Hyperplasia in the Anterior Mediastinum: A Case Report and Review of the Literature - Hyang-im Lee; In-seok Jang; Kyung Nyeo Jeon; Gyung Hyuck Ko; Jong Sil Lee; Dong Chul Kim; Dae Hyun Song; Jeong-Hee Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Thymoma is the most common neoplasm of the anterior mediastinum and has malignant potential. Germ cell tumors (GCTs) found in the anterior mediastinum are usually benign, and malignant GCTs, such as seminomas, are rare. Histologically, mediastinal seminoma is indistinguishable from testicular seminoma except for site-associated morphological features such as lymphoid follicular hyperplasia. Therefore, excluding metastasis is very important. Recently, we treated a young adult patient with multiple thymic masses that occurred simultaneously. The patient underwent a thymectomy for the removal of the mediastinal masses, one of which was diagnosed as type B2 invasive thymoma, and two of which were diagnosed as primary mediastinal seminomas with massive follicular hyperplasia. The patient received adjuvant chemotherapy after surgical resection. To our knowledge, this is the first description of a thymoma and a mediastinal seminoma occurring simultaneously in the thymus. We present this case along with a literature review.